Effect of core working memory training on consecutive interpreting - Bahraman, Mostafa; Movahed, Roya (Universidade Estadual Paulista, 2021)
Interpreting seems to be one of the most demanding and complex language tasks, whose performance is dependent heavily on working memory (WM). This study attempts to examine the effect of WM training on the improvement of consecutive interpreting. To this end, 20 students of Translation Studies at Kashmar Higher Education Institute were selected. The participants’ skill in interpretation was rated by implementing an interpretation scale.  Then, all the participants received instructions on how to expand their WM capacity through core working memory training. The group went through another evaluation session after the treatment. The results were analyzed by running a paired sample t-test.  It was found that WM capacity expansion exercises had a significant effect on the accuracy subscale whereas target language quality and delivery, the other two subscales, proved minor and no improvements, respectively.  The findings of the present study can be used to train interpreters or even in any other of educational setting which requires attention and memory skills.